(untitled) (Medico Legal Update, 2020)
In health services, the drug can save lives and improve health quality. So the provision of essential medicines is mandatory and requires government support at all levels, both central, provincial and Regency/city. The existence of such support can be activities, budgets and commitments. The purpose of this research is to know the system of drug planning in the technical implementation Unit of the Regional Office of Medicine management in Ambon City Health office. This type of research is a qualitative study. Data collection is done through in-depth interviews, observation and document study. Information collected from 6 people who are involved in the management of drugs in the technical implementation Unit of the Regional Office of the Department of Medicine of the city Health office in Ambon. The results showed that drug planning uses a special team with the calculation of drug needs using method of consumption. The emptiness and excess medication are still common due to the change in public health centers affecting the drug prescribing patterns. Therefore, it needs a good coordination between the planning team in the technical implementation Unit of the regional office of the District Health Care office in Ambon City with a doctor at the Public health center in the area to be obedient in writing prescriptions according to the medication that has been ordered.